XLN306 induces apoptosis in human breast carcinoma MX-1 cells - Jing Jin; Li-na Zhu; Hai-jing Zhang; Yan Li; Yi Zhang; Wan-qi Zhou; Bai-ling Xu; Xiao-guang Chen (Elsevier, 2011)
XLN306 is a novel synthetic quinazoline derivative with potentially useful anticancer activity. In previous research, we showed that XLN306 is highly cytotoxic to many tumor cell lines. This paper reports an investigation of this cytotoxicity in a number of human carcinoma cell lines. The results show that human breast carcinoma MX-1 cells are extremely sensitive to XLN306 and that the cytotoxicity is due to dose- and time-dependent apoptosis as confirmed by DAPI stain and DNA fragmentation analysis. Both extrinsic and intrinsic pathways are involved in the apoptosis process. The findings indicate that XLN306 has apoptotic induction activity and may be useful for the management of various cancers, especially breast carcinoma.